The effect of the guided discovery learning model on students' mathematical reflective thinking skills - Adinda Putri Salsabila; Sugeng Sutiarso; Santy Setiawati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
Students’ mathematical reflective thinking skills remain limited, particularly in understanding problems, connecting mathematical concepts, evaluating solution processes, and drawing conclusions when solving linear equations in one variable. This quasi-experimental study investigated the effect of guided discovery learning on students’ mathematical reflective thinking skills. The population comprised 183 eighth-grade students at SMP Negeri 2 Sumberejo. Through cluster random sampling, class VIII.2, comprising 30 students, was selected as the experimental group, while class VIII.3, comprising 31 students, was selected as the control group. A pretest-posttest control group design was employed, and data were collected using a test of mathematical reflective thinking skills. Improvement was measured using N-Gain scores and compared through an independent-samples t-test. The experimental group obtained a higher mean N-Gain score (0.62) than the control group (0.54). The hypothesis test also showedthat the calculated t-value (2.65) exceeded the critical value (1.67) at the 5% significance level. These findings indicate that guided discovery learning produced a significantly greater improvement in students’ mathematical reflective thinking skills than conventional learning, particularly in connecting concepts and evaluating solutions.